The Effectiveness of Group Guidance Services in Minimizing Smartphone Addiction - Anita Erlisa; Nurussakinah Daulay (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Smartphone addiction is a problem among students in the technology era. This has become increasingly unstoppable since online learning during the Covid-19 pandemic. In this context, guidance from adults (teachers or parents) is needed for children (students). This study aims to determine the effectiveness of group guidance services in minimizing smartphone addiction. The background of this research is at MTs Nurul Islam Indonesia, specifically the research subjects, namely 30 students of class IX2 for the academic year 2021/2022 to test how big the level of smartphone addiction is among students, between before and after being given group guidance services. The type of this research is counseling guidance action research (PTBK), carried out in 2 cycles. Data analysis was carried out quantitatively using questionnaires and observations. The results of this study indicate the level of smartphone addiction of IX2 MTs Nurul Islam Indonesia students when a pre-test was held on 8 students (26.7%), 2 students in the high category, and 6 students in the very high category. Furthermore, in the first cycle, group guidance services were provided through group discussions, lectures, questions and answers, and filling out questionnaires. There were 2 students (6.7%) who were still addicted to smartphones in the high category and 4 students in the medium category, 2 students in the low category. In cycle II, 1 student (3.3%) was still addicted to smartphones in the high category, 3 students in the low category, and 4 students in the very low category. Thus, it was concluded that the level of smartphone addiction in students decreased after being given counseling services.